Prehistoric lifestyles on Gotland – Diachronic and Synchronic perspectives - Martinsson-Wallin, Helene; Wallin, Paul; Apel, Jan (Archaeologia Lituana, 2011)
The prehistoric period of Gotland Island covers around 8000 years of human occupation. In this paper we will concentrate on the period from the initial colonization to the end of the Bronze Age, a period of c. 7000 years. The prehistory of the people, who populated the Island of Gotland during this time, is diversified and reflects a variety of activities and lifestyles, which are influenced and interact with different regions around the Baltic Sea. The cultural traits seen in the material culture point to various contacts spheres over time. So far we do not have any conclusive evidences if the initial Mesolithic groups, whom were the pioneers to Gotland, settled here on a permanent basis and could be considered as the original ancestors of the Gotlandic people. This is something that was suggested by Österholm (1989). It seems more likely that various groups of settlers have arrived in Gotland at different times and/or that it has been a constant flow of goods and genes both from the Scandinavian and Baltic areas during the investigated time span. Throughout these 7000 years this region has also experienced dramatic environmental changes, which have affected the living conditions and patterns of subsistence for the groups of people living here. In this paper we will discuss different prehistoric lifestyles and the question of origin of the people living on Gotland. This is done in the light of our new research where we are compiling and re-analyzing old data as well as working with some specific case studies carrying out new excavations. [...]